Assessment the Planning by Using Gamma Knife Indices for the Patient with Vestibular Schwannoma (Iraqi Journal of Medical Sciences, 2024)
Background: Stereotactic radiosurgery (SRS) is the use of a high dosage of radiation, usually to an intracranial target. Healthy brain tissue often surrounds the target when therapies are delivered inside the skull, and this is usually the main organ that is at risk (OAR). To reduce the possibility of normal tissue toxicity and its associated side effects, it is imperative to establish a steep dosage falloff from the target's periphery to normal tissue when using these kinds of treatments.Objective: To evaluate the plans of vestibular Schwannoma using the latest version of gamma knife “lightning by estimating the correlation between the overall sphericity degree and, most important the evaluation parameters such as coverage, selectivity, homogeneity index (HI), selectivity, gradient index (????I), and shot density. Methods: A cross-sectional study. The sphericity degree (?) was determined by using planning for each target volume (TV) of the fifty patients who had stereotactic radiosurgery (SRS) performed on them in order to treat vestibular schwannoma, Calculating this parameter required developing a theoretical concept for operational sphericity, which was done and following are some of the measurements that are used in the analysis of the values that were found: coverage (????), selectivity (S), gradient index (????I), Paddick conformity index (????I Paddick), and dosage distribution (IV/TV).Results: The mean age of patients was 44.54±11.93 years ranging from (20-80) years and the prevalence of females in this study was 35 (70%) more than the males 15 (30%). The prescribed dose for vestibular Schwannoma patients was 12????y. The mean target volume is 5.367±0.058 cm3, ranging from (0.079-26.497) cm3. This study showed that dividing the tumor into 2 spheres, the first sphere delineates the regular part of the tumor, and the second sphere is delineated irregular cancer components, since the reference plan is a spherical target, the degree of sphericity is an excellent parameter to use when evaluating the dose distribution of a plan for the treatment of vestibular Schwannoma.Conclusion: According to the findings of this study, dividing the tumor into two spheres provides valuable information regarding the dose distribution both inside and outside the desired volume. Keywords: Stereotactic radiosurgery, Acoustic neuromas, gradient index, selectivity, coverageCitation: Jasim MH, Abdullah SS, Faraj MK. Assessment the planning by using gamma knife indices for the patient with vestibular Schwannoma. Iraqi JMS. 2024; 22(1): 13-19. doi: 10.22578/IJMS.22.1.2
Keywords: Stereotactic radiosurgery; Acoustic neuromas; gradient index; selectivity; coverage